The Structure of Local Public Finance and the Quality of Life - Gyourko, Joseph; Tracy, Joseph (Journal of Political Economy, 1991)
Differences in local fiscal conditions generate compensating differentials across local land and labor markets just as the authors have known amenities to do. Thus, the local fiscal climate affects the quality of life across metropolitan areas. The authors present new results showing that intercity fiscal differentials are nearly as important as amenity differentials in determining the quality of life across urban areas. The paper also investigates the sensitivity of the quality-of-life rankings with respect to assumptions about the nature of the marginal entrant. The authors estimate a random effects model to account for city-specific error components in the housing and wage regressions. Copyright 1991 by University of Chicago Press.